The development of the German labour market after World War II - Hansjörg Herr; Bea Ruoff (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
Labour market developments have Germany undergone two shocks: German reunification in the early 1990s, and the Hartz reforms in the early 2000s. They separated the German labour market into the traditional rather corporatist labour market segment, characterised by a high degree of coordination, and a new, less regulated labour market segment. The latter is characterised by low wages and precarious working conditions. A precariat living under conditions of high uncertainty developed. All these developments are mainly the result of legal changes in Germany - changes which, with respect to employment creation, were unneeded.
Keywords: J50; J51; O11; 330; labour markets; Germany; Hartz reforms; German unification